Novel Splicing of Immune System Thyroid Stimulating Hormone β-Subunit—Genetic Regulation and Biological Importance - Klein, John R. (Frontiers in Endocrinology, 2019)
Thyroid stimulating hormone (TSH), one of four glycoprotein hormones produced by the anterior pituitary, consists of an α-subunit and a β-subunit. Within the hypothalamus-pituitary-thyroid axis, TSH regulates the secretion of the thyroid hormones, thyroxine (T4) and triiodothyronine (T3). It has been known for several decades that TSH is produced by the cells of the immune system; however, the functional significance of that remains unclear. We identified a novel splice variant of TSHβ (TSHβv) that is primarily made by bone marrow hematopoietic cells and peripheral leukocytes. Recent studies have linked TSHβv functionally to a number of health-related conditions, including enhanced host responses to infection and protection against osteoporosis. However, TSHβv also has been associated with autoimmune thyroiditis in humans. Yet to be identified is the process by which the TSHβv isoform is produced. Here, a series of genetic steps is laid out through which human TSHβv is generated using a series of novel splicing steps that result in a transcript in which exon 2 is deleted, all of exon 3 is incorporated, and the 3’ end of intron 2 is used to code for a twenty-three amino acid signal peptide. It is expected that this information will contribute considerably to our understanding of how immune system TSHβv is regulated in health and disease.